2004
DOI: 10.1128/mcb.24.10.4361-4371.2004
|View full text |Cite
|
Sign up to set email alerts
|

Focal Adhesion Kinase Suppresses Apoptosis by Binding to the Death Domain of Receptor-Interacting Protein

Abstract: Focal adhesion kinase (FAK) is a nonreceptor protein tyrosine kinase that plays a key role in maintaining focal adhesion function and cell survival and is implicated in cell migration, adhesion, and cell cycle control (9,13,18,20,33,44). Overexpression of FAK is a common event in numerous tumor systems, including breast, colon, and thyroid carcinomas (2,24,32,41), and occurs at early stages of tumorigenesis, before a tumor has developed the capacity for invasion and metastasis (2). Importantly, FAK has been sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
137
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(145 citation statements)
references
References 41 publications
7
137
1
Order By: Relevance
“…This further supports the role of FAK as a survival signal. 39 In this study, high FAK expression had a borderline association with positive lymph node status and stage at diagnosis. Owing to the low number of patients presenting with stage III and IV disease we cannot confirm this association in this study.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This further supports the role of FAK as a survival signal. 39 In this study, high FAK expression had a borderline association with positive lymph node status and stage at diagnosis. Owing to the low number of patients presenting with stage III and IV disease we cannot confirm this association in this study.…”
Section: Discussionmentioning
confidence: 52%
“…38 Recent work has shown FAK association with receptor-interacting protein, a serine/threonine kinase that contains a death domain. 39 When FAK binds to receptor-interacting protein, the proapoptotic signals supplied by receptor-interacting protein are suppressed. This further supports the role of FAK as a survival signal.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a correlation between STATl expression and cisplatin resistance in cell lines derived from patients with ovarian carcinoma was also reported (Roberts et al, 2005), and inhibitors of the STATl pathway have been shown to induce apoptosis in leukaemic cells from patients (Martinez-Lostao et al, 2005). The pathway analysis showed that STATl is positively influenced by MAPK1 and FAK, two of the most highly connected resistance-associated genes, both of which have been reported to inhibit apoptosis (Shimada et al, 2002;Kurenova et al, 2004). Notably, STATl expression has been reported higher in tumour compared with corresponding normal tissue for a wide range of tumour types (www.oncomine.com).…”
Section: Discussionmentioning
confidence: 91%
“…There are suggestions that interfering with cell spreading may be a method of sensitizing tumor cells to TRAIL killing (13)(14)(15). Spreading is mediated by the interaction of integrins with extracellular matrix components.…”
Section: Introductionmentioning
confidence: 99%